Wheat agriculture and family ties - Ang, James (2020)
Several recent contributions to the literature have suggested that the strength of family ties is related to various economic and social outcomes. For example, Alesina and Giuliano (2014) highlight that the strength of family ties is strongly correlated with lower GDP and lower quality of institutions. However, the forces shaping family ties remain relatively unexplored in the literature. This paper proposes and tests the hypothesis that the agricultural legacy of a country matters for shaping the strength of its family ties. Using data from the World Values Survey and the European Values Study, the results show that societies with a legacy of cultivating wheat tend to have weaker family ties. Analysis at the sub-national level (US data) and the country level corroborate these findings. The estimations allow for alternative hypotheses which propose that pathogen stress and climatic variation can potentially also give rise to the formation of family ties. The results suggest that the suitability of land for wheat production is the most influential factor in explaining the variation in the strength of family ties across societies and countries.